WSCC: Social and Emotional Climate and Physical Environment. Issue 2 (12th February 2022) - Goh, Tan Leng; Egan, Cate A.; Merica, Christopher B.
Abstract: The social and emotional climate and the physical environment components of the Whole School, Whole Community, Whole Child (WSCC) model contribute to promoting a safe and nurturing learning environment in PK–12 schools. In this article, the authors review research on the social and emotional climate and the physical environment over the past decade. Recommendations for health and physical education (HPE) teachers to lead, promote, implement, and sustain these components in schools, as well as practical examples are provided. Strategies for HPE Teacher Education programs that prepare preservice teachers to lead and promote these components in schools are also presented.